A Rare Paraneoplastic Syndrome of Lung Cancer - R. Azzeddine; L. Herrak; A. Rhanim; A. Jniene; M. Elftouh; L. Achachi (Case Reports in Pulmonology)
Achalasia is a neurodegenerative motor disease of the esophagus resulting mainly from a loss of function of the lower esophageal sphincter, the pathophysiology of which is still poorly understood. Its incidence is rare—it is 1.6 per 100,000—and its occurrence in the context of paraneoplastic syndrome has been rarely described in the literature. We report a rare case of paraneoplastic achalasia associated with lung cancer.